2019
DOI: 10.20448/journal.522.2019.52.369.373
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pilates, Step and Zumba Exercises on Self-esteem, Happiness and Communication Skill Levels

Abstract: The aim of this study is to examine the self-esteem, happiness and communication skills of women who participated in pilates, step and zumba exercise programs. A total of 54 women participated in the study. Pilates, step and zumba exercise program was applied three days a week for a total of 12 weeks. As a data col lection tool in research; personal information form, Rosenberg self-esteem scale consisting of 10 items, which was adapted to Turkish by Cuhadaroğlu (1986) the scale of communication skills created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…In a study examining the effects of Zumba and Pilates exercises on communication skills, happiness and self-esteem, Özdenk and Imamoglu (2019) have noted that Pilates significantly increases communication skills, happiness and self-esteem, which are closely linked to selfcompassion. Recent studies have also shown that self-compassion is intrinsically associated with mindfulness, and mindfulness promotes greater self-compassion (Bluth & Blanton, 2014).…”
Section: Pilates Life Satisfaction Mindfulness and Self-compassionmentioning
confidence: 99%
“…In a study examining the effects of Zumba and Pilates exercises on communication skills, happiness and self-esteem, Özdenk and Imamoglu (2019) have noted that Pilates significantly increases communication skills, happiness and self-esteem, which are closely linked to selfcompassion. Recent studies have also shown that self-compassion is intrinsically associated with mindfulness, and mindfulness promotes greater self-compassion (Bluth & Blanton, 2014).…”
Section: Pilates Life Satisfaction Mindfulness and Self-compassionmentioning
confidence: 99%
“…Penelitian ini menyimpulkan bahwa zumba berpengaruh positif terhadap tingkat kebahagiaan dan kemampuan berkomunikasi. Para peneliti ini juga merekomendasikan para wanita untuk mengikuti olahraga zumba, step, dan pilates (Özdenk & Imamoglu, 2019). Kedua penelitian tersebut di atas dapat menjadi dasar yang kuat untuk mengembangkan perencanaan pesan dalam membangun citra Zumba Fitness di Indonesia.…”
Section: "Kita Bisa Mengadakan Audit Perception Semacam Fgd Atau Surv...unclassified